Capacity enhancement in communication system via NNRR - Aziz, M. S.; Afroozeh, A.; Roslan, M. S.; Jalil, M. A.; Nawi, I. N.; Ali, J.; Yupapin, P. P. (My University, 2011)
We present the effect of the FSR on capacity of communication system. A new novel system of soliton generation using a 1.30 μm optical Gaussian pulse in a nonlinear nano-ring resonator (NNRR) system forms the soliton pulse train. The soliton pulse wavelength with center wavelength at 1.30 μm is generated after a powerful Gaussian soliton pulse is input into the NNRR system, we propose a system that can be used to solve many problems in communication systems. The results show that we how do receive the free spectrum range (FSR) by NNRR. This is obtained via the add/drop filter, which can be used to increase the channel capacity in the communication network. In this paper the best FSR is 0.052 nm. This result allows the channel capacity expanding due to the abundance of propagation spacing from the soliton collision.
Keywords: Free Spectrum Range; Gaussian Soliton; Nonlinear Nano-ring Resonator